Unusual formation and sub-omohyoid course of external jugular vein. - Sirasanagandla, SR; Narendra, P; Satheesha, NB; Somayaji, SN; Kumar, MR Bhat; Surekha, DS; Jyothsna, P (Department of Surgery, UKM Medical Centre, 2013)
Variations in the origin and termination of external jugular vein are common and are reported in the past. However, variations in the course of external jugular vein are uncommon. During routine dissection classes for medical undergraduates, we came across the unusual formation and course of right external jugular vein and absence of common facial vein, in an approximately 60-year-old male cadaver of Indian origin. External jugular vein was formed by the continuation of undivided trunk of retromandibular vein. Following its formation, it passed vertically superficial to sternocleidomastoid muscle to the lower part of occipital triangle. In the occipital triangle it pierced the investing layer of deep cervical fascia and passed deep to the inferior belly of omohyoid muscle and coursed through the subclavian triangle. Then, it terminated at the junction of subclavian vein with internal jugular vein. Facial vein joined with submental vein and finally drained into internal jugular vein. Further, the posterior auricular vein and anterior jugular veins were absent. Knowledge about the variations of the retromandibular vein, common facial vein and external jugular vein observed in this study, may be important for the surgeons, to prevent inadvertent injury and excessive bleeding during diagnostic and therapeutic procedures.